“Peace with the Earth” in the Context of the Decade to Overcome Violence - Kerber, Guillermo (The ecumenical review, 2011)
In this article, Guillermo Kerber situates theWorld Council of Churches' Decade to Overcome Violence against the background of debates about war and peace that have taken place within the ecumenical movement since the Second World War. He shows how this initiative has contributed to an understanding of the concept of “just peace” that goes beyond being the opposite of “just war, but rather demands the absence of all forms of structural violence, including gender-based, cultural and media violence”. Against this background, this article underlines the need for an ecological understanding of “peace with the earth” to be an integral part of such a “just peace”.